Mutant Sod1-Expressing Astrocytes Release Toxic Factors That Trigger Motoneuron Death by Inducing Hyperexcitability - Madrid-Montecinos, R; Rojas-Montecinos, P (American Physiological Society, 2013)
Amyotrophic lateral sclerosis (ALS) is a devastating paralytic disorder caused by dysfunction and degeneration of motoneurons starting in adulthood. Recent studies using cell or animal models document that astrocytes expressing disease-causing mutations of human superoxide dismutase 1 (hSOD1) contribute to the pathogenesis of ALS by releasing a neurotoxic factor(s). Neither the mechanism by which this neurotoxic factor induces motoneuron death nor its cellular site of action has been elucidated. Here we show that acute exposure of primary wild-type spinal cord cultures to conditioned medium derived from astrocytes expressing mutant SOD1 (ACM-hSOD1G93A) increases persistent sodium inward currents (PCNa), repetitive firing, and intracellular calcium transients, leading to specific motoneuron death days later. In contrast to TTX, which paradoxically increased twofold the amplitude of calcium transients and killed motoneurons, reduction of hyperexcitability by other specific (mexiletine) and nonspecific (spermidine and riluzole) blockers of voltage-sensitive sodium (Nav) channels restored basal calcium transients and prevented motoneuron death induced by ACM-hSOD1G93A. These findings suggest that riluzole, the only FDA-approved drug with known benefits for ALS patients, acts by inhibiting hyperexcitability. Together, our data document that a critical element mediating the non-cell-autonomous toxicity of ACM-hSOD1G93A on motoneurons is increased excitability, an observation with direct implications for therapy of ALS. © 2013 the American Physiological Society.